a-Thalassemia trait caused by frameshift mutations in exon 2 of the a2-globin gene: HBA2:c.131delT and HBA2:c.143delA - Finlayson, J.; Ghassemifar, Reza; Holmes, P.; Grey, D.; Newbound, C.; Pell, N.; Jennens, M.; Greenwood, L.; Beilby, J. (2012)
We describe two frameshift mutations associated with an a-thalassemia (a-thal) phenotype, identified in three unrelated individuals investigated for persistent microcytosis. The first mutation, HBA2:c.131delT, is located in codon 43, and the second, HBA2:c.143delA, is located in codon 47. Both are due to single base pair deletions that cause a frameshift and a premature termination codon (PTC) at positions 48/49. The presence of a PTC at this position has been documented to result in nonsense mediated mRNA decay that would account for the thalassemic phenotype.